Formation of COOH-Ylides, and Their Reactivities and Selectivities in Wittig Reactions - Suganuma, Yuta; Kobayashi, Yuichi (Synlett, 2019)
Whereas two equivalents of base are typically required to prepare carboxylate (CO2–) ylides [Ph3P+C–(H)-alk-CO2–] (alk = alkanediyl) from carboxy (CO2H) phosphonium salts [(Ph3PCH2-alk-CO2H)+] X–, we reveal, for the first time, that carboxy ylides [Ph3P+C–(H)-alk-CO2H] can be generated with one equivalent of NaHMDS at 0 °C, and that the Wittig reaction of simple aliphatic aldehydes (1 equiv) with these carboxy ylides (1.5–2 equiv) in THF at –95 to –90 °C for one hour, then at warming temperatures to 0 °C over two hours affords (Z)-alkenoic acids. Phosphonium salts containing (CH2)n alkanediyl chains (n = 2–5) showed adequate reactivity and high Z-selectivity, whereas shorter or longer alkanediyl chains resulted in a low Z-selectivity and/or a low yield. On the basis of these results with different (CH2)n chains and that obtained with a rigid methylene group, we propose that a rapid equilibrium between Ph3PCH2-alk-CO2– and Ph3P+C–(H)-alk-CO2H, through an intramolecular hydrogen exchange, accounts for the success of the Wittig reaction.
Keywords: Wittig reaction; carboxy phosphonium salt; carboxy ylides; carboxylate ylides; alkenoic acids